One more factor joins the plot: Pbx1 regulates differentiation and survival of midbrain dopaminergic neurons - Castro, Diogo S (The EMBO journal, 2016)
Midbrain dopaminergic neurons have been the subject of intense research, because of their importance in pathologies such as Parkinson's disease. In this issue of The EMBO Journal , Villaescusa et al ( 2016 ) show the transcription factor Pbx1 is required for the differentiation and survival of midbrain dopaminergic neurons. Notably, Pbx1 protects from oxidative stress by inducing Nfe2l1, and the expression of both genes is reduced in dopaminergic neurons from Parkinson's patients. This is an important study, with possible implications in regenerative medicine and drug design. Graphical Abstract The homeobox transcription factor Pbx1 regulates dopaminergic neuronal development and protects them from oxidative stress.